The geography of intergenerational mobility: Evidence of educational persistence and the "Great Gatsby Curve" in Brazil - Tharcisio Leone (German Institute of Global and Area Studies (GIGA), 2019)
This paper explores the variation in intergenerational educational mobility across the Brazilian states based on Markov transition matrixes and univariate econometric techniques. The analysis of the national household survey (PNAD-2014) confirms a strong variation in mobility among the 27 federative units in Brazil and demonstrates a significant correlation between mobility and income inequality. In this sense, this work presents empirical evidence for the existence of the "Great Gatsby curve" within a single country: states with greater income disparities present higher levels of persistence in educational levels across generations. Finally, I investigate one specific mechanism behind this correlation - namely, whether higher income inequality might lead to a lower investment in human capital among children from socially vulnerable households. The paper delivers robust and compelling results showing that children born into families where the parents have not completed primary education have a statistically significant reduction in their chance of completing the educational system if they live in states with a higher level of income inequality.
Keywords: J62; I24; I26; 330; intergenerational mobility; Great Gatsby curve; educational attainment; human capital; school dropouts; inequality; Brazil